Integrating 21st Century Skills into Teaching Medical Terminology (Journal of Pedagogical Inventions and Practices, 2022)
The article begins with the disambiguation of the keywords we will use to show how coordinating the 21st century abilities into showing English for specific Purposes increase on both the understudies' capacity to obtain English and their scope of abilities, capacities and mentalities that are needed to work and live in a informational society. Consequently, understudies can apply what they realize during their English illustrations to their primary field of concentrate just as to life. They figure out how to convey successfully in reality and develop critical thinking and other viable, genuine abilities, for example, concentrate on abilities and composing strategies.